Cognitive-motor interference during gait in patients with Multiple Sclerosis: a mixed methods Systematic Review. (November 2018) - Postigo-Alonso, B.; Galvao-Carmona, A.; Benítez, I.; Conde-Gavilán, C.; Jover, A.; Molina, S.; Peña-Toledo, M.A.; Agüera, E.
Highlights: Multiple Sclerosis (MS) patients show significant Cognitive-motor interference (CMI). The most sensitive motor variable detecting significant CMI in MS was double support. Verbal Fluency proved to be sensitive and also specific to CMI in MS patients. Clinical usefulness of CMI in the assessment of patients with MS is mentioned. Abstract: Background: Cognitive-motor interference (CMI) has been proposed as a valid marker of daily life impairment in Multiple Sclerosis (MS). The heterogeneity and scarce number of studies regarding CMI in MS has hampered the synthesis of the existing evidence. The present systematic review employed a mixed methods approach with the aim of identifying and describing variables under which CMI is particularly useful to assess patients with MS. Results: MS patients showed significant CMI. The motor variables that were most sensitive in detecting significant CMI were velocity (m/s), cadence (steps/min), and double support (% gait cycle), which was also specific for MS. Among the cognitive tasks, Alternate Alphabet and Serial Subtracting 7 s were sensitive, whereas Verbal Fluency were both sensitive and specific to CMI in MS. Conclusions: CMI should be assessed in MS with a standardised dual task such as the Verbal Fluency task while walking, with measurements of the double support time and the effect on the cognitive task. The clinical usefulness of CMI in the assessment of patients with MS is discussed.